Fungsi Tembang dalam Seni Pertunjukan Tari - Maryono Maryono (Institut Seni Indonesia Surakarta, 2010)
The existence of song in a dance performance does not function simply a musical instrument but rather more comprehensively is a medium which has a great potential for expressing the content or meaning of the dance, which in turn contains a message that is intended to be communicated. It would appear that the existence of song in a dance performance is also an aesthetical medium of expression. The position of song in the performing arts has a number of highly strategic functions, namely: 1) as a medium of expression for the dancers, 2) as a musical element, and 3) as a pointer to content or meaning. The understanding of these three functions of song is based more on the strength, contribution, and support of the potential which is able to bring a dance performance to life. It should be realized that song in a dance performance is a highly significant expression of competence, and for this reason, the way in which it is treated and presented needs to be examined in greater depth in order to discover its true meaning.Keywords : song, function, and dance